Pendampingan Digital Marketing Bagi Ibu PKK di Desa Pandankrajan Kec. Kemlagi Kab. Mojokerto Terkait Pelatihan ES Coklat Kakao - Ni Dewi Ambal Ikka; Nabila Ayunda Cahyani; Rahmadhani Sulistyowati Pasha; Dhimas Saputra; Pressy Jati Amerta; Nazila Rohmatul Aula; Al Kautsar Maskur; Ella Nur Aini; Erisa Ayu Kusumaning Tyas; Heru Sutrisno; Indah Permata Sari; Intan Lailatul Husna; Muhammad Reza Alfian; Muhammad Reza Satria Inggil; Muhammad Rizky Habibie; Nanda Ul-yana Putri Akmali; Naufal Hafizh; Nuzula Nur Aida; Puji Rahayu; Riqlatus Sitta Wahyu; Rudiansyah Saputra; Shalama Qowlam Fadila; Wisjayanti Tri Anggeliani; Zahra Venti Amelia; Yunan Maulana Fichry (Jurnal Nusantara Berbakti, 2025)
Chocolate cocoa ice is one of the popular beverage products among consumers, especially among teenagers and children. In facing tight competition, it is essential for producers to analyze effective marketing strategies and calculate the Cost of Goods Sold (COGS) to ensure business sustainability. This analysis aims to evaluate the marketing strategies employed, including promotions, distribution, and pricing. Additionally, calculating COGS is necessary to understand the costs involved in production and to determine competitive selling prices. The research method used is descriptive with a qualitative approach, involving socialization, assistance, and training. The results of the study indicate that effective marketing strategies, such as leveraging social media and conducting promotional activities in the surrounding area, can enhance product visibility. The calculation of COGS provides a better understanding of production costs, allowing managers to set competitive selling prices. From this analysis, it is hoped that recommendations can be provided for the PKK group to optimize marketing strategies and cost efficiency, enabling the chocolate cocoa ice business to grow and positively impact the local economy. This research can also serve as a reference for similar businesses in other regions.